2017
DOI: 10.3897/natureconservation.35.12761
|View full text |Cite
|
Sign up to set email alerts
|

The LIFE Project “Monitoring of insects with public participation” (MIPP): aims, methods and conclusions

Abstract: The Life Project “Monitoring of insects with public participation” (LIFE11 NAT/IT/000252) had as the main objective to develop and test methods for the monitoring of five beetle species listed in the Annexes of the Habitats Directive (92/43/EEC): Osmodermaeremita (hermit beetle, Scarabaeidae), Lucanuscervus (European stag beetle, Lucanidae), Cerambyxcerdo (great capricorn beetle, Cerambycidae), Rosaliaalpina (rosalia longicorn, Cerambycidae) and Morimusasper/funereus (morimus longicorn, Cerambycidae). The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…At a European level, it has been shown that this silvicolous species prefers semishaded and semi-open habitats characteristic of mature and old forests (Jurc et al 2008, Solano et al 2013, Carpaneto et al 2017). According to Rossi de Gasperis et al 2016, this species showed a preference for huge fallen trees, branches on the ground, a low percentage of debarked surface and high canopy closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a European level, it has been shown that this silvicolous species prefers semishaded and semi-open habitats characteristic of mature and old forests (Jurc et al 2008, Solano et al 2013, Carpaneto et al 2017). According to Rossi de Gasperis et al 2016, this species showed a preference for huge fallen trees, branches on the ground, a low percentage of debarked surface and high canopy closure.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation mainly targeted large trees (both alive and degraded), stumps and fallen trunks, as the most favourable woody material to host individuals from the investigated species (Jurc et al 2008, Fusu et al 2015, Carpaneto et al 2017 (Fig. 2).…”
Section: Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collection of individuals was performed during the monitoring of R. alpina carried out in the framework of the EU LIFE-MIPP Project (Campanaro et al 2017;Carpaneto et al 2017;Rossi De Gasperis et al 2017) in two Italian National Parks (also "Sites of Community Importance" or SCI): "Foreste Casentinesi, Monte Faltenora e Campigna" National Park (hereafter abbreviated as "FC"; SCI: IT4080001), located in the Northern Apennines (Forlì-Cesena and Arezzo provinces), and "Abruzzo Lazio e Molise" National Park (hereafter abbreviated as "PA"; SCI: IT7110205), located in the Central Apennines (L'Aquila, Isernia and Frosinone provinces). The distance between the two areas is about 250 km.…”
Section: Study Areas Sample Collection and Dna Extractionmentioning
confidence: 99%
“…The study area within the FC corresponded to the locality "Foresta della Lama" (700 m asl; 43.4312°N, 11.8381°E), characterized by closed forests dominated by Fagus sylvatica and Abies alba. In PA, three sub-areas were selected: "Difesa di Pescasseroli" (DP; 1300 m asl; 41.8461°N, 13.8600°E), and "Val Fondillo" (VF; 1200 m asl; 41.7841°N, 13.9563°E), characterized by pure beech forests with wide clearings and old growth trees (the distance between these two subareas is about 6.5 km); and "Zio Mas" (ZM; 1700 m asl; 42.0802°N, 14.0566°E), characterized by fragmented beech woodlands interspersed among open mountain grasslands (distant~10 and 30 km from VF and DP, respectively; for more detail on the ecological features of the sampling areas see Carpaneto et al 2017). The sample tissues for molecular analysis were obtained over a 2year sampling period (2014-2015, during July and August), from specimens caught on trees along specific sampling transects (for details on positions of "wild trees" and the areas covered by the sampling transects, see figs 6 and 7 in Campanaro et al 2017).…”
Section: Study Areas Sample Collection and Dna Extractionmentioning
confidence: 99%